Seismic Isolation for Protecting Historical Buildings: A Case Study - D'Amato, Michele; Gigliotti, Rosario; Laguardia, Raffaele (Frontiers in Built Environment, 2019)
The protection of cultural heritage from seismic risk is an open issue due to the difficulties in finding technical solutions allowing a balance between their effectiveness and invasiveness. Among the available protection techniques, seismic isolation is one of the most suitable obtaining a significant performance improvement by acting on a limited portion of the structure. In this paper, it is shown an application of such technique on a reinforced concrete frame building catalogued as of historical interest by Italian Ministry of Cultural Heritage. It was realized in 30’s representing the “Modern Style” of Italian Architecture, also known as Italian Rationalism, and designed only for vertical loads without any specific regulation for lateral loads. Geometry, material properties and reinforcements characteristics have been derived from an extensive investigation campaign. By the means of a FEM 3D model they are simulated among them the seismic responses of both existing and retrofitted building through a seismic isolation system composed by elastomeric and sliding isolators. Furthermore, a new methodology for estimating the seismic capacity exhibited by the structure in the past is presented and applied.